CD28-negative cytolytic effector T cells frequently express NK receptors and are present at variable proportions in circulating lymphocytes from healthy donors and melanoma patients. - Speiser, D; Valmori, D; Rimoldi, D; Pittet, M; Liénard, D; Cerundolo, V; MacDonald, H; Cerottini, J; Romero, P (1999)
In humans, NK receptors are expressed by natural killer cells and some T cells, the latter of which are preferentially alphabetaTCR+ CD8+ cytolytic T lymphocytes (CTL). In this study we analyzed the expression of nine NK receptors (p58.1, p58.2, p70, p140, ILT2, NKRP1A, ZIN176, CD94 and CD94/NKG2A) in PBL from both healthy donors and melanoma patients. The percentages of NK receptor-positive T cells (NKT cells) varied strongly, and this variation was more important between individual patients than between individual healthy donors. In all the individuals, the NKT cells were preferentially CD28-, and a significant correlation was found between the percentage of CD28- T cells and the percentage of NK receptor+ T cells. Based on these data and the known activated phenotype of CD28- T cells, we propose that the CD28- CD8+ T cell pool represents or contains the currently active CTL population, and that the frequent expression of NK receptors reflects regulatory mechanisms modulating the extent of CTL effector function. Preliminary results indicate that some tumor antigen-specific T cells may indeed be CD28- and express NK receptors in vivo.